2011
DOI: 10.1203/pdr.0b013e31821d06a1
|View full text |Cite
|
Sign up to set email alerts
|

An Initial Sustained Inflation Improves the Respiratory and Cardiovascular Transition at Birth in Preterm Lambs

Abstract: A sustained inflation (SI) facilitates lung aeration after birth but may impair the neonatal cardiovascular transition. We aimed to determine the effect of an initial SI on pulmonary arterial and carotid blood flow (PBF and CBF) after preterm birth. Fetal sheep were instrumented at ϳ122 d of gestation (d). Lambs were delivered at ϳ127 d and received either an initial SI (40 cm H 2 O for 1 min or until a volume of 20 mL/kg was administered) followed by ventilation for 30 min (SI; n ϭ 7) or ventilation for 30 mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
131
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(141 citation statements)
references
References 21 publications
10
131
0
Order By: Relevance
“…Review apart from reduced vascular permeability (Figure 4) (4,48), suggesting that simply improving the initial respiratory care in the delivery room may reduce brain injury.…”
Section: Respiratory Support and Brain Injurymentioning
confidence: 99%
“…Review apart from reduced vascular permeability (Figure 4) (4,48), suggesting that simply improving the initial respiratory care in the delivery room may reduce brain injury.…”
Section: Respiratory Support and Brain Injurymentioning
confidence: 99%
“…PEEP is essential in the preterm lung (5,14). In our study, we used a PEEP (8 cmH 2 O) previously shown to be appropriate in preterm lambs (6,11,16,17), and higher than that used in similar animal studies (5,9,10,14,15,20,29), suggesting our results are due to differences in recruitment strategy and not subsequent ventilator management.…”
Section: Discussionmentioning
confidence: 86%
“…In our study using intubated preterm lambs, we systematically describe the interrelationship between the use of antenatal corticosteroids, exogenous surfactant therapy, and two distinct recruitment strategies applied Unlike previous animal studies of respiratory care at birth (6,(10)(11)(12)15,16,(20)(21)(22)(27)(28)(29)(30), our study involved a large sample size. Pooling all epochs, the use of an OLV stepwise PEEP approach significantly improved C dyn and oxygenation compared to a 30-s 40 cmH 2 O SI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations